Growth characterization and chemical composition of the cell wall of native species of bamboos - Parma, Daniele de Freitas (2017)
Bamboos are predominant plants in forest areas and it have become a favorite choice for carbon sequestration to absorb atmospheric CO 2 and restorer additive balance of the Earth’s climate system, due to its high growth rate compared to most other plant species. Furthermore, the bamboos are used to produce pulp and paper or charcoal and active carbon for special purposes. Furthermore, it has ecological and environmental functions in soil erosion control, water conservation and land rehabilitation. Thus, the quantification of its biomass provide among other things, an estimate of cellulosic material provide a potential source of renewable energy and base for carbon sequestration studies. Thus, the aim of this study were (i) Estimate biomass and carbon storage is Merostachys species (M. fischeriana, M. tatianae and), in order to understand its distribution along different compartments (foliage, branches and culm). (ii) Evaluate biomass models according to biometric variables collected - circumference and diameter of the culm at the base and at the height of the breast, total height and number of nodes. (iii) Quantify moisture and carbon content. (iv) Identify and quantify the main components of the culm cell wall - cellulose, hemicellulose, lignin and ash. To quantify the productivity of M. fischeriana, M. tatianae and M. ximenae, twenty individuals of each specie were collected in Atlantic forest area in Southeastern Brazil. The plants were measured, cut, weighed and dried. To quantify the chemical components of the culm cell wall, three samples (base, medium and apex) of each of the five individuals of the three species were lyophilized and homogenized to obtain fine powder (40-60 mesh). The design of nested factors comparing the areas with each other and within each species was used. The allocation of biomass in Merostachys species was higher in the culm, with detection of some interspecific differences. Individual dry biomass correlates strongly with biometric variables the culm base diameter, diameter at breast height and total height. Thus, simple regression models, considering only those independent variables fit well to express the individual total dry weight as the dependent variable. The productivity of Merostachys with culture spaced 3m x 3m is highly competitive with other species of bamboo cultures; even with other plants (i.e. Pinus). Merostachys has an average daily growth rate of 0.07 m, reaching its maximum height in four months and its full development, with leaves and branches, 6-9 months. The moisture content is decreasing from the base toward the apex, as well as in relation to age. We verified that there was no significant difference between the content of cellulose, hemicellulose, lignin and ash between species of Merostachys as well as between the base, middle and apex. However, only M. tatianae presented significant differences (p = 0.0026) for the lignin concentration between regions. The average concentration of cellulose in Merostachys fischeriana, M. tatianae and M. ximenae ranged from 78-82%. In Merostachys the value found for holocellulose was higher than 98%, being this value related to the cellulose concentration, since the observed hemicellulose content is congruent with that verified for other species of bamboo. The lignin content was 0.86-1.06%. The ashes concentration between 0.52-0.68% was similar to that observed for some species of Eucalyptus. Studies of quantification of the chemical components of bamboo cell wall are rare. Comprehensive knowledge of biomass and chemical components in the bamboo species will facilitate the use of materials in the forestry industrial sector and help to enhance their utilization in the chemical and biochemical related industry. In addition, these results can be supporting taxonomic and ecological studies.